A Cross-Docking Framework for Supply Chain Logistics in Production Scheduling - Yu, Hongnian; Thapa, Gyan Bahadur (Journal of Institute of Science and Technology, 2015)
Synchronization of all partners along a supply chain logistics system is one of the challenges in most of the business operations. In this paper, we present a brief literature review of cross-docking approaches for supply chain logistics problem. On describing the problem, we formulate the supply chain logistics problem as a truck sequencing problem to minimize the discrepancies of operation times of inbound and outbound trucks. The problem is decomposed in two sub-problems as inbound and outbound parts as a solution strategy. Journal of Institute of Science and Technology, 2014, 19(1): 39-44